2012
DOI: 10.1007/s00411-012-0417-x
|View full text |Cite
|
Sign up to set email alerts
|

Micronuclei in human peripheral blood lymphocytes exposed to mixed beams of X-rays and alpha particles

Abstract: The purpose of this study was to analyse the cytogenetic effect of exposing human peripheral blood lymphocytes (PBL) to a mixed beam of alpha particles and X-rays. Whole blood collected from one donor was exposed to different doses of alpha particles ((241)Am), X-rays and a combination of both. All exposures were carried out at 37 °C. Three independent experiments were performed. Micronuclei (MN) in binucleated PBL were scored as the endpoint. Moreover, the size of MN was measured. The results show that exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
35
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 61 publications
7
35
0
Order By: Relevance
“…This could be due to differences in the protocols and slide preparation methods employed. However, in our previous publication we observed similar levels of MN as in the present investigation [18]. …”
Section: Discussionsupporting
confidence: 90%
“…This could be due to differences in the protocols and slide preparation methods employed. However, in our previous publication we observed similar levels of MN as in the present investigation [18]. …”
Section: Discussionsupporting
confidence: 90%
“…The consequences of this delay are not clear, since 24 h after irradiation the levels of IRIF were similar for all irradiation schemes. However, it is worthwhile to note that our earlier study showed a higher than predicted level of micronuclei in mixed beam-exposed human peripheral blood lymphocytes [46]. There we also speculated that DNA repair is impaired in cells exposed to a mixed beam.…”
Section: Discussionmentioning
confidence: 62%
“…The rational for using these doses was that in our earlier study we saw a synergistic effect of mixed beams in this dose range [46]. For analysis of repair kinetics 0.27 Gy alpha particles, 0.8 Gy X-rays and 0.13 + 0.40 Gy mixed beams (of alpha particles and X-rays, respectively) were the chosen doses.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…IR-induced clustered damage two of the donors. The study is a continuation of our analyses of cellular effects of simultaneous exposure to alpha radiation and X-rays [18,[20][21][22][23]].…”
Section: Introductionmentioning
confidence: 99%